Aircraft Technology 2018
DOI: 10.5772/intechopen.76009
|View full text |Cite
|
Sign up to set email alerts
|

Stator-Rotor Interaction in Axial Turbine: Flow Physics and Design Perspective

Abstract: The stator-rotor interaction is an important issue in turbomachinery design when the highest performances are targeted. Different characters mark the interaction process in high-pressure or low-pressure turbines depending both on the blade height and on the Reynolds number. For small blade heights, being the stator secondary flows more important, a more complex interaction is found with respect to the high blades, where the stator blade wake dominates. In low-pressure turbines, the stator wake promotes the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…For instance, LI value of R2-1 at a specific time and desired CLP, such as CLP4, represents the R2-1 loading in comparison to an averaged-LI of the all blades of the second rotor computational domain in CLP4 and CLP1. For example, the loading index for R2-1 blade at t/T = 0 is mathematically shown by equation (17). Figure 22 shows time-dependent LI variations for the second rotor blades at their mid-span in CLP4 and CLP1 cases.…”
Section: Clocking Effects On Performancementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, LI value of R2-1 at a specific time and desired CLP, such as CLP4, represents the R2-1 loading in comparison to an averaged-LI of the all blades of the second rotor computational domain in CLP4 and CLP1. For example, the loading index for R2-1 blade at t/T = 0 is mathematically shown by equation (17). Figure 22 shows time-dependent LI variations for the second rotor blades at their mid-span in CLP4 and CLP1 cases.…”
Section: Clocking Effects On Performancementioning
confidence: 99%
“…Through researches on rotor-stator blades rows interactions in a twin-shaft turbine, Gaetani concluded that the maximum efficiency can be achieved when the upstream wake impinges on the next stator blade leading edge. 17 He also concluded that at low Reynolds numbers, upstream wakes causes transition to occur while they interact with the blade suction side boundary layer. Although, this transitional flow causes the losses to increase, it makes the boundary layer to encounter with streamwise adverse pressure gradient, and as a result, prompts the flow separation point to move downstream.…”
Section: Introductionmentioning
confidence: 99%
“…tends to create a narrow blade at the suction side of the blade domain. This is expected as vortex generation from the pressure side is different from the suction side (Gaetani, (Gaetani 2018)). According to the fluid nature of entering through the cavity, e.g.…”
Section: Rotor Examplementioning
confidence: 99%